Of toothy grins and angry snarls-open mouth displays contribute to efficiency gains in search for emotional faces - Horstmann, G.; Lipp, Ottmar; Becker, S. (2012)
The emotional face-in-a-crowd effect is widely cited, but its origin remains controversial, particularly with photorealistic stimuli. Recently, it has been suggested that one factor underlying the guidance of attention by a photorealistic emotional face in visual search might be the visibility of teeth, a hypothesis, however, that has not been studied systematically to date. The present experiments manipulate the visibility of teeth experimentally and orthogonally to facial emotion. Results suggest that much of the face-in-a-crowd effect with photorealistic emotional faces is due to visible teeth, and that the visibility of teeth can create a search advantage for either a happy or an angry target face when teeth visibility and facial emotion are confounded. Further analyses clarify that the teeth visibility primarily affects the speed with which neutral crowds are scanned,shedding new light on the mechanism that evokes differences in search efficiency for different emotional expressions. © 2012 ARVO.